2018
DOI: 10.1111/cpr.12480
|View full text |Cite
|
Sign up to set email alerts
|

A novel inhibitor of ADAM17 sensitizes colorectal cancer cells to 5‐Fluorouracil by reversing Notch and epithelial‐mesenchymal transition in vitro and in vivo

Abstract: A novel ADAM17 inhibitor ZLDI-8 may be a potential chemosensitizer which sensitized CRC cells to 5-fluorouracil or irinotecan by reversing Notch and EMT pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 57 publications
2
35
0
Order By: Relevance
“…To our knowledge, this study is the first report that ADAM9 overexpression promotes the cell proliferation, migration, and invasion in TNBC cells by activating the AKT/NF-κB pathway. ADAM9 expression was increased in tumor tissues from TNBC patients and TNBC cells compared with the non-TNBC tumor tissues and cell lines, which is consistent with the previous finding that ADAM9 was overexpressed and associated with a more aggressive phenotype of breast cancer (26). Interestingly, MCF-10A (a normal epithelial breast cell line) expresses relatively high ADAM9 expression than non-TNBC cell lines, which might be caused by the culture method of immortalized MCF-10A cell line.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…To our knowledge, this study is the first report that ADAM9 overexpression promotes the cell proliferation, migration, and invasion in TNBC cells by activating the AKT/NF-κB pathway. ADAM9 expression was increased in tumor tissues from TNBC patients and TNBC cells compared with the non-TNBC tumor tissues and cell lines, which is consistent with the previous finding that ADAM9 was overexpressed and associated with a more aggressive phenotype of breast cancer (26). Interestingly, MCF-10A (a normal epithelial breast cell line) expresses relatively high ADAM9 expression than non-TNBC cell lines, which might be caused by the culture method of immortalized MCF-10A cell line.…”
Section: Discussionsupporting
confidence: 90%
“…Besides, several members of ADAMs were reported to involve in epithelial-mesenchymal transition (EMT) processes in cancer. ADAM12 is participated in TGF-β mediated EMT in breast cancer, while ADAM17 induces EMT in colorectal cancer via Notch signaling pathway (25,26). In this study, we found that ADAM9 expression is upregulated in TNBC cells and patients compared with the non-TNBC.…”
Section: Discussionmentioning
confidence: 48%
“…Downregulation of the activity of the Notch signaling pathway by various pathways can reduce the resistance of cells to various damaging factors. This increases the sensitivity of cells to molecular targeted drugs and offers safer and more effective treatments (i.e., cytotoxic chemotherapy drugs and radiation therapy) [64][65][66][67] .…”
Section: Discussionmentioning
confidence: 99%
“…pathway (Li et al, 2018), and induces metastasis in gastric cancer through activation of Notch and Wnt signaling pathways (Li et al, 2019c). A review article discussed ADAM17 inhibitors for inflammation and cancer therapy (Kanda et al, 2017).…”
Section: Analysis Of Genetic Alterations Of the Pbmentioning
confidence: 99%